(untitled) (Journal of Applied Learning and Teaching, 2024)
This paper outlines the conceptual, strategic and implementation framework that underpins the Scholarship of Learning and Teaching (SoLT) in an Australian non-university higher education provider. The standards for scholarly practice that lie at the heart of this framework are outlined, and the linkages between the related concepts of scholarship, research, professional development, and quality improvement are explored. An organisation-wide SoLT Strategy drives scholarly activities, while an implementation framework provides support and incentives that include guidelines and templates, mentoring and professional development, blanket ethics approval for the use of students’ and staff’s natural data with an online mechanism for managing consent, small funding grants, and awards for scholarly practice. SoLT is granted equal status with discipline-based research in promotion and tenure. The faculty produce and disseminate annual scholarly outputs and report annually on the impact of scholarly activities, which are monitored through academic governance committees. The initiative has proved successful, with 89 and 91 percent, respectively, of academics producing scholarly outputs that met the institute’s standards for scholarly practice in the first two years of operation. The framework offers a comprehensive and coherent approach that may assist other higher education providers seeking to elevate the status and activity level of SoLT.